An examination of patients' responses to framework breaks in psychotherapy in an institutional context - Rees, Christopher Lewis (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
This study examines the workings of the ground rules which make up the framework of psychotherapy, in an institutional context, by analysing transcripts of twelve audio taped sessions of therapy conducted in a psychiatric hospital. The breaks in the ground rules of the sessions are noted and the patients' responses to these breaks are analysed using Langs's (1982, 1988) method for decoding patients' material, suitably modified for use as a hermeneutic research method. Although all of the ground rules are broken in the institutional context, only one of the ten ground rules appears to be essentially affected by this particular institutional context. Other ground rules are broken out of choice of technique or through error. The institutional context has a structural impact only on the ground rule requiring a one to one relationship with privacy and confidentiality and this ground rule is transgressed in a number of ways in all twelve sessions examined in this study. However the patients' responses to this breach only occur in ways predicted by communicative theory when the break in the ground rule involves actual entry into the therapy space by another person. Other contraventions to this ground rule that do not involve such an entry do not elicit the predicted patient responses. The many other ground rule breaks occurring in the institutional context evoke the predicted responses in the patients' material. In the study, no therapist interventions are found to comply with the communicative therapy requirements for sound interventions; concomitantly it was found that no therapist interventions receive the required derivative validation. The results indicate that it is possible to conduct therapy of a substantially secure frame variety in this institutional context with minimum effort on the part of therapists and given proper training and supervision of therapists in the techniques of communicative psychotherapy. Furthermore the results lend weight to the importance of the communicative methodology for listening to patients' material in psychotherapy in an institutional context. However, further rigorous study of competently performed therapy, executed within the context of a secure frame within an institutional context, is needed in order to demonstrate the benefits of the communicative psychotherapy interventions and interpretations in this context.
Keywords: Psychotherapy patients; Psychotherapy -- Research; Psychotherapy -- Case studies; Psychiatric hospital care